2018
DOI: 10.1002/gch2.201800001
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Water Harvesting with Optimized Solar Thermal Membrane Distillation Device

Abstract: Water distillation with solar thermal technology could be one of the most promising way to address the global freshwater scarcity, with its low cost and minimum environmental impacts. However, the low liquid water productivity, which is caused by the heat loss and inadequate heat utilization in solar‐thermal conversion process, hinders its practical application. Here, a compact solar‐thermal membrane distillation system with three structure features: highly localized solar‐thermal heating, effective cooling st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
98
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 35 publications
0
98
0
Order By: Relevance
“…29 Although this concept has already been widely deployed in the large-scale multipleeffect distillation plants 4 and some conventional solar stills, 30 realizing effective enthalpy recycling in small-scale systems with solar heat localization poses significant technological challenges. Few recent studies have demonstrated portable systems with solar heat localization which recycled vaporization enthalpy to generate electricity (with 1.23% electricity conversion efficiency 25 ), drive extra evaporation (with 72% 31 and 138% 32 total solar-to-vapor conversion efficiencies), or produce fresh water and electricity simultaneously (with 4110% solar-to-vapor conversion efficiency and 11% electricity conversion efficiency 33 ). However, the demonstrated solar-to-vapor conversion efficiency -slightly above 100%is still limited in comparison to what is theoretically achievable.…”
mentioning
confidence: 99%
“…29 Although this concept has already been widely deployed in the large-scale multipleeffect distillation plants 4 and some conventional solar stills, 30 realizing effective enthalpy recycling in small-scale systems with solar heat localization poses significant technological challenges. Few recent studies have demonstrated portable systems with solar heat localization which recycled vaporization enthalpy to generate electricity (with 1.23% electricity conversion efficiency 25 ), drive extra evaporation (with 72% 31 and 138% 32 total solar-to-vapor conversion efficiencies), or produce fresh water and electricity simultaneously (with 4110% solar-to-vapor conversion efficiency and 11% electricity conversion efficiency 33 ). However, the demonstrated solar-to-vapor conversion efficiency -slightly above 100%is still limited in comparison to what is theoretically achievable.…”
mentioning
confidence: 99%
“…For instance, a novel photothermal MD module was constructed by two steps: deposition of Mxene on the hydrophobic PVDF membranes via vacuum-filtration process, followed by a dip coating of PDMS. [171] As a consequence, the two-level distiller could achieve distillate productivity as high as 1.02 kg m −2 h −1 with a solar efficiency of 72% upon one sun illumination. [175] However, aforementioned MXene coating struggles to low adhesion to the PVDF membrane.…”
Section: Photothermal-assisted Membrane Distillationmentioning
confidence: 99%
“…2019, 6, 1900883 Figure 10. [171] Copyright 2018, Wiley-VCH. a) Schematic illustration of conventional MD and novel photothermal MD with localized heating at the membrane surface.…”
Section: Photothermal-assisted Membrane Distillationmentioning
confidence: 99%
“…[ 8 ] Moreover, the condensate collector will be heated up over time and reduce the condensation efficiency. [ 9 ] Consequently, high vaporization rate cannot be simply translated into effective water harvesting. These concerns can be addressed by utilizing a hydrophobic microporous membrane to separate the feedwater and the collected water vapor, which preferentially condenses away from the light path.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,10 ] By implementing the thermal localization concept using solar absorber nanomaterials will reduce the energy input for heating the feeding water, and also enlarge the temperature gradient across the membrane thereby improving its efficiency. [ 9,11 ]…”
Section: Introductionmentioning
confidence: 99%